Study of Measles in Children and How to Eliminate It - hamed, Hiba adnan; Mohammed, Ban sattar; Alosh, Zahraa Muaen; abd, Aya suhail (American Journal of Botany and Bioengineering, 2024)
Measles is a highly contagious disease caused by a virus. It spreads easily when an infected person breathes, coughs, or sneezes. It can cause severe illness, complications, and even death. Measles can affect anyone, but it is most common in children. However, the actual death toll may be higher. Measles affects the respiratory system and then spreads throughout the body. Symptoms include fever, cough, runny nose, and a rash all over the body. Vaccination is the best way to prevent getting measles or passing it on to other people. The vaccine is safe and helps your body fight the virus. Before the measles vaccine was introduced in 1963 and vaccination became widespread, major epidemics occurred roughly every two to three years and killed an estimated 2.6 million people each year. An estimated 136,000 people died from measles in 2022 — most of them children under the age of five — despite the availability of a safe and cost-effective vaccine.